1994
DOI: 10.3382/ps.0730236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Maternal Thyroid Status on Embryo Physiology and Hatchability of Commercial Turkey Eggs

Abstract: Fertile turkey eggs produced by commercial hens fed iodine or triiodothyronine were compared with those from hens fed a control diet to observe the effects of the maternal thyroid status on the energy budget of turkey eggs. Dietary iodine improved hatchability, decreased the number of dead pips, and maintained blood glucose concentrations during pipping and hatching with less reliance on hepatic gluconeogenesis (as assessed by glucose-6-phosphatase activity) compared with controls. Hatchability of eggs from he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Beneficial effects on the embryonic metabolism, efficiency of glucose utilization, and tissue differentiation are possible but not exclusive explanations. For example, studies in commercial strains of turkeys showed that supplementation of iodine, a critical and perhaps limiting component of THs (Hsu et al, 2016), in the maternal diet increased egg hatchability (Christensen and Davis, 2001;Christensen and Donaldson, 1994), and increased embryonic gluconeogenesis that helped maintain blood glucose concentrations (Christensen and Donaldson, 1994). However, in Japanese quails, orally T4-dosed females laid eggs containing high yolk T3 and T4 levels but those eggs did not have higher hatching success than controls (Wilson and McNabb, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects on the embryonic metabolism, efficiency of glucose utilization, and tissue differentiation are possible but not exclusive explanations. For example, studies in commercial strains of turkeys showed that supplementation of iodine, a critical and perhaps limiting component of THs (Hsu et al, 2016), in the maternal diet increased egg hatchability (Christensen and Davis, 2001;Christensen and Donaldson, 1994), and increased embryonic gluconeogenesis that helped maintain blood glucose concentrations (Christensen and Donaldson, 1994). However, in Japanese quails, orally T4-dosed females laid eggs containing high yolk T3 and T4 levels but those eggs did not have higher hatching success than controls (Wilson and McNabb, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the effects of preincubation conditions, such as breeder age and nutrition, storage time, and egg weight on overall embryo development (Christensen and Donaldson, 1994;Vieira and Moran, 1998a, b;Tona et al, 2004). It is known that storage time and breeder age affect egg quality and consequently hatchability and chick quality.…”
Section: Introductionmentioning
confidence: 99%
“…Esse calor aumenta com o desenvolvimento do pinto e a temperatura interna alcança 101,75°F (38,75°C) no décimo dia de incubação. No momento do nascimento, a temperatura interna dos ovos está ao redor de 103,5°F (39,7°C), o que corresponde aproximadamente à temperatura alcançada pelos ovos na incubação natural(MARQUES, 1994).SegundoCHRISTENSEN (1994), depois da fertilização, o embrião é continuamente afetado pelo ambiente. Variáveis como: temperatura, umidade relativa, ventilação, viragem dos ovos, posição dos ovos e a luz, devem ser controladas para uma ótima incubação.…”
unclassified